Diagnosis and medical treatment of otitis externa in a ragdoll cat: A case report - Usrina, Nora; Habibie, Maulana; Darmawi, Darmawi; Amiruddin, Amiruddin; Zulkifli, Baidillah; Yusriani, Yenni (The International Journal of Tropical Veterinary and Biomedical Research, 2023)
Otitis is a disease that is often found due to the cat's ears being unclean and causing earwax to build up along with fluid. Otitis is caused by inflammation of the epithelium of the ear canal and also surrounding structures such as the external auditory meatus and pinna. A 3-month-old Ragdoll cat, male, with white and black hair on the ears, was examined with complaints of head tilting and frequent head shaking, pus in the ears, and inflammation. Clinical examination revealed erythema. The ear wax swab examination results showed an Otodectes cynotis mite infection. The results of the bacterial culture examination showed the presence of Klebsiella sp bacterial infection. The animal was diagnosed with otitis externa. Treatment for otitis externa is given by Dexamethasone, Erlamycetin (Chloramphenicol 1%), Ivermectin, and lidocaine. The accumulated earwax is also cleaned using a cotton bud and saline. Five days after therapy the cat showed recovery.